PELAKSANAAN REDISTRIBUSI TANAH PERTANIAN DAN PENSERTIFIKATANNYA DI DESA SUNGAI PANTAI KECAMATAN RANTAU BADAUH KABUPATEN BARITO KUALA PROPINSI KALIMANTAN SELATAN - , NORMANSYAH, Agus Sudaryanto, SH.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research is to study the implementation of a redistribution of agricultural lsnd snd certificate in the village of the sungai pantai Kecamatan Rantau Badauh District Barito Kuala and to study what it becomes an obstacle in the implementation of a redistribution of agricultural land and certificate in the village of the sungai pantai kecamatan rantau badauh district barito kuala. This is the kind of research juridical empirical research, so that data main is a primer that collected data obtained from field studies. To furnish data also conducted research libelary to obtain data secondary. The determination of the sample use sampling techniques purposive. Now the subject of his research respondents a number of 3 person and speakers a number of a person. The research found that first, the implementation of a redistribution of agricultural ground as the stalk is done in some stages which include counseling. inventorying acceptance benefits, the recipient, selection of a candidate the mapping, controlling decree a certificate oa a haven and the control over the land as many as 879 the field of 1.273 hectares in order to improve the economy farmers and access to reform, the owner of land especially in the village of the river pantai sub-district seacost badauh district barito drilling, second constraits in the implementation of a redistribution of land object landreform in the village river pabtai sub-district seacost badauh is absentee (demesne lands farm outside sub-district), there who diverted befire 10 years becouse secured a permit head land office, the pegs marker lots not mounted pmna based on number 3/1997, obtained also the fact that not all participants a redistribution of land object landreform many as farmers and commonly very difficult to find state land freely or the lands in criteria have qualify.